2004
DOI: 10.1016/j.physe.2003.11.214
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous excitation of spins and pseudospins in the bilayer ν=1 quantum Hall state

Abstract: The tilting angular dependence of the energy gap was measured in the bilayer quantum Hall state at the Landau level filling ν = 1 by changing the density imbalance between the two layers. The observed gap behavior shows a continuous transformation from the bilayer balanced density state to the monolayer state. Even a sample with 33 K tunneling gap shows the same activation energy anomaly reported by Murphy et al. [1]. We discuss a possible relation between our experimental results and the quantum Hall ferromag… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
14
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 17 publications
5
14
0
Order By: Relevance
“…[4] that introducing a parallel component of the magnetic field allows determination of the spin of the lowest-lying charged excitations by the increase in the activation energy with parallel field. The experimental results indicated that the excitations at ν = 1 are accompanied with seven electron spin flips, while at ν = 3 and 5 only a single spin flips [4,10]. This is consistent, in principle, with the predictions of the skyrmion approach.…”
Section: Introductionsupporting
confidence: 83%
See 1 more Smart Citation
“…[4] that introducing a parallel component of the magnetic field allows determination of the spin of the lowest-lying charged excitations by the increase in the activation energy with parallel field. The experimental results indicated that the excitations at ν = 1 are accompanied with seven electron spin flips, while at ν = 3 and 5 only a single spin flips [4,10]. This is consistent, in principle, with the predictions of the skyrmion approach.…”
Section: Introductionsupporting
confidence: 83%
“…[3,4,5,6,7,8,9,10]). Strongly enhanced values of the spin gap in the 2D electron system in GaAs/AlGaAs heterostructures were found by measurements of the activation energy for the longitudinal resistivity minimum at filling factor ν = 1, 3, and 5 [3,4,5].…”
Section: Introductionmentioning
confidence: 99%
“…11,14,15 It seems that the exchange energy has been underestimated by making the derivative expansion. It is necessary to go beyond the present approximation to fully understand the problem.…”
Section: ͑831͒mentioning
confidence: 99%
“…Terasawa et al 15 have measured the activation energy by controlling the tilting angle ⌰ at the balanced point in a sample with ⌬ SAS Ӎ 33 K. We have fitted their data [ Fig. 6] by the ppinexcitation formula (9.11) and by the generic formula (9.15).…”
Section: ͑919͒mentioning
confidence: 99%
See 1 more Smart Citation